2008
DOI: 10.1002/ccd.21552
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcomes of real‐world experience using sirolimus‐eluting stents in saphenous vein graft disease

Abstract: Our results support that SES used in SVG lesions result in a reduction in TLR without an increased risk of mortality, and therefore may be an equally safe and feasible technique for revascularization with excellent long-term clinical outcomes. These patients may benefit from prolonged dual antiplatelet and statin medication regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 25 publications
1
22
1
Order By: Relevance
“…Tables 1, 2 and 3 summarize the characteristics of the studies. The other 26 studies (n = 7347) were observational registries [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43]…”
Section: Resultsmentioning
confidence: 99%
“…Tables 1, 2 and 3 summarize the characteristics of the studies. The other 26 studies (n = 7347) were observational registries [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42], [43]…”
Section: Resultsmentioning
confidence: 99%
“…However, there is a paucity of prospective data on DES in SVG interventions, although BMS is associated with high restenosis rates in SVG lesions. The results of mostly retrospective observational series comparing DES with BMS in SVGs have been conflicting: 6 studies showed better results with DES (9 -14) and 9 suggested no difference between BMS and DES (15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 97%
“…We used the abstracted MACE as defined by the authors; however, the definition varied among studies. For mortality, some studies used all-cause mortality (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27), whereas others used cardiac mortality (28 -32). Some studies used TVR (20 -22,24 -27,29,32-35), whereas others used TLR (28,30,31,36) or both (18 -20,24,37) in their composite MACE end point.…”
Section: Data Analysis Meta-analysesmentioning
confidence: 99%